De Novo Collapsing Glomerulopathy in Renal Allograft in Association with BK Virus Nephropathy in a Child and Stabilization of Renal Function by Elimination of Viremia - Gera, D. N. (Indian J Nephrol, 2017)
Well-recognized association between HIV 1 infection and collapsing glomerulopathy (CG) raises the possibility that intrarenal infection by other viruses may also contribute to the development of this lesion in native or post-transplant kidneys. There is evidence in literature about association of these lesions with cytomegalovirus, Epstein–Barr virus, hepatitis C virus, and parvovirus B19 infections. Here, we present a case report of post-transplant BK virus nephropathy in a male child who was found to have CG in subsequent biopsy 2 months later. His renal function and proteinuria were stabilized on elimination of viremia.